Stephen Crane's use of color terms in the red badge of courage - Marcon, Robert Victor C. (College of Arts and Letters, University of the Philippines Diliman, 1989)
This thesis presents a study of the use of color terms in Stephen Crane's war novel The Red Badge of Courage. The investigation of color terms was done by relegating the different meanings of a particular color term. This led to a better understanding and appreciation of the war novel. The use of color terms by Stephen Crane showed how his war novel carried much meaning through the metaphorical uses. His fragmentary episodes were connected by them. On the whole, the use of color terms successfully gave the war novel The Red Badge of Courage a color of Stephen Crane's mastery of impressionistic writing.